2021
DOI: 10.1177/17590914211019443
|View full text |Cite
|
Sign up to set email alerts
|

Metabolism-Based Gene Differences in Neurons Expressing Hyperphosphorylated AT8− Positive (AT8+) Tau in Alzheimer’s Disease

Abstract: Metabolic adaptations in the brain are critical to the establishment and maintenance of normal cellular functions and to the pathological responses to disease processes. Here, we have focused on specific metabolic pathways that are involved in immune-mediated neuronal processes in brain using isolated neurons derived from human autopsy brain sections of normal individuals and individuals diagnosed as Alzheimer’s disease (AD). Laser capture microscopy was used to select specific cell types in immune-stained thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 81 publications
0
5
0
Order By: Relevance
“…The p values were computed with nSolver and adjusted for multiple comparisons using the Benjamini‐Hochberg method. Adjusted p values were not used for thresholding differentially expressed genes, however 30 . Visual representations of gene analysis were generated using the nSolver and Graphpad Prism (version 9).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The p values were computed with nSolver and adjusted for multiple comparisons using the Benjamini‐Hochberg method. Adjusted p values were not used for thresholding differentially expressed genes, however 30 . Visual representations of gene analysis were generated using the nSolver and Graphpad Prism (version 9).…”
Section: Methodsmentioning
confidence: 99%
“…Adjusted p values were not used for thresholding differentially expressed genes, however. 30 Visual representations of gene analysis were generated using the nSolver and Graphpad Prism (version 9).…”
Section: Gene Expression Analysismentioning
confidence: 99%
“… 94 Recently, it has been shown that the gene expression level of RSAD1 increased apparently in the brain tissues from individuals diagnosed as Alzheimer’s disease. 95 Besides the important roles of RSAD1 from animals, the members from plants also appear to be functional, as has been revealed by transcriptomic analysis. 96 In vitro studies showed that RSAD1 firmly binds heme, as a typical heme absorption spectrum was clearly observed in the human RSAD1-heme complex, 90 suggesting that RSAD1 likely has a heme chaperone activity similar to HemW.…”
Section: Other Hemn-like Proteinsmentioning
confidence: 95%
“…Removing the RSAD1 gene in zebra fish embryos causes serious dysfunctional development, suggesting RSAD1 is required for survival . Recently, it has been shown that the gene expression level of RSAD1 increased apparently in the brain tissues from individuals diagnosed as Alzheimer’s disease . Besides the important roles of RSAD1 from animals, the members from plants also appear to be functional, as has been revealed by transcriptomic analysis …”
Section: Other Hemn-like Proteinsmentioning
confidence: 95%
“…A new perspective regarding tau toxicity is that it has the potential to disrupt cellular metabolism [206,207]. Tau deposition is correlated with impaired metabolisms of glucose, norepinephrine, and purine [208,209], reduced glucose utilization and oxidative phosphorylation activity [209,210], as well as the interference of the arginine, ornithine, and methionine metabolisms [211]. Although the metabolic decline in AD can be attributed to the synergistic effect of Aβ and tau [207], it is plausible that tau itself exerts a significant influence on inducing metabolic disturbances.…”
Section: Revisiting the Pathogenic Mechanisms Of Tau Toxicitymentioning
confidence: 99%